Developing a Strong and Diverse Nonprofit Board - Micayla Richardson; Marlen Barajas Espinosa; Jennifer A. Jones; Kimberly Wiley (EDIS)
This publication aims to provide strategic direction to nonprofit leaders who want to develop their board of directors. It defines and describes board diversity, then explains how to recruit and maintain a diverse board. Written by Micayla Richardson, Marlen Barajas Espinosa, Jennifer A. Jones, and Kimberly Wiley, and published by the UF/IFAS Department of Family, Youth and Community Sciences, May 2022.